Academic Relational Positioning in EFL Higher Education: Lexico-Pragmatic Development Across Digitally Mediated Interaction - Nurhikmah, Andi; Syam, Anugerah Febrian (Borneo Journal of Language and Education, 2026)
In the increasingly digitalized era of higher education, digital academic communication spaces have become a primary arena for the formation of academic identity and legitimacy. Although studies on EFL communicative competence and digital pragmatics continue to grow, few studies have explored micro-longitudinally how lexico-pragmatic development contributes to the formation of academic relational positioning in digitally mediated academic interactions. This study aims to investigate the trajectory of this development in the context of EFL higher education. The study employed an ethnographically informed longitudinal qualitative inquiry design involving 12 students and 2 lecturers over one semester. Data in the form of authentic archives of digital interactions (WhatsApp groups and LMS) were collected through systematic archiving and analyzed using a theoretically informed qualitative analysis grounded in positioning theory and relational work. The results show a shift from formulaic minimalism to collocational alignment, an expansion of the lexico-pragmatic repertoire, and a more contextual and strategic relational orchestration stage. These findings confirm that the development of academic competence is not solely linguistic, but also relational and institutional. This study concludes that digitally mediated interaction is a crucial space for the process of academic discourse socialization in digitalized higher education.